GEOLOGI, ALTERASI DAN MINERALISASI EMAS EPITERMAL SULFIDASI RENDAH DI DAERAH TAMBANG SAWAH, LEBONG, PROVINSI BENGKULU - Muhammad Muhsin Al Hakim; Arifudin Idrus; Wiwit Suryanto (KURVATEK, 2022)
Abstract –– Tambang Sawah Area, Lebong Regency, Bengkulu Province, is geologically located in the Barisan mountains and Sumatra fault zone. The prospect of Tambang Sawah area lies in the physiography of the central Sumatran mountains ranges composed by the igneous rocks of the Sunda – Banda magmatic arc. This study is aimed to understand the deposit geology and ore characteristics of the gold deposit at the study area. Quartz vein mineralization of Tambang Sawah occurred in granite rock intruded into andesitic breccia rocks, with the geological structure of mineralization control in the form of joint, breccia, dike, and fault, namely the Ketahun fault that forms extentional fracture zones which were filled by hydrothermal fluid in form of quartz veins. Hydrothermal alterations that appear at the study site are typical types of alterations found in epithermal gold deposits, namely, argillic, silicified and propylitic. Sulfide minerals markers of low sulfidation epithermal type gold deposits found, namely, pyrite, calcopyrite, covelite, sphalerite and galena with colloform vein texture, cockade-crustiform, moss, and brecciated texture. Gold is interpreted to be derived from the deposition of sulfide minerals and the deposition of quartz veins, the level of gold in rocks and veins varies greatly with an average 4,8 ppm. Based on the results of ore geochemical analysis of positively correlated gold with elements Ag, Cu, Pb and Zn. Keywords: Mineralization, low sulfidation epithermal gold, Tambang Sawah, Lebong, Bengkulu.